Pengembangan Antarmuka Website Dengan Menggunakan Metode Goal Directed Design (Studi Kasus: PT. Focus Inservindo) - Arif Ramadhan; Hanifah Muslimah Az-Zahra; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PT. Focus Inservindo or FOCUS is an organization that helps Small and Medium Enterprises (SMEs) entrepreneurs in providing guarantees from both insurance and banks. FOCUS wants the development of websites in appearance aspect and additional pages and features to increase the credibility of the website so that it helps companies to expand the scope of businesses and networks and it is expected that company profits can increase. This study produced a FOCUS website design using the Goal Directed Design method. The method has six phases to provide solutions for website design based on company goals. The research phase begins, to determine the needs of stakeholders and users. The modeling phase, to produce a user model in the form of persona to describe the general user group. Requirement definition stage, to generate 19 lists of website requirements and website environmental requirements. Design framework phase, to produce a sitemap as an overview of information structure and produce a website interface design in the form of wireframe. Design refinement phase, to produce a high-fidelity prototype that is ready for testing. Stage design support, to test the prototype that has been produced. Testing is done by means of user testing and is done to FOCUS website users, both as corporate clients and non-clients. In addition, the SUPR-Q questionnaire was used to assess usability, credibility, appearance and loyalty aspects. the results obtained, the overall aspects worth 77.04% (category C) are of good value so that it can be interpreted that the website developed is good and acceptable (acceptable) by the user.